Vortex-induced Vibration of a Flexible Free-hanging Circular Cantilever - Prastianto, R. W.; Otsuka, K.; Ikeda, Y. (ITB Journal Publisher, LPPM ITB, 2009)
TheÂ behaviorÂ ofÂ aÂ free-hangingÂ riserÂ ofÂ floatingÂ offshoreÂ structures would be different fromÂ aÂ typical at-sea-floor-terminated riser type of oil or gas platforms.Â For the design purpose, the present studyÂ was intended to incorporate someÂ importantÂ factorsÂ of the riser conditionsÂ (i.e.Â bidirectional vibration,Â freeend condition, and spanwise variation of response amplitude) for investigating its dynamicsÂ characteristics.Â AnÂ experimentalÂ investigationÂ onÂ time-dependent motionÂ ofÂ aÂ flexible free-hanging circular cantileverÂ subjected to uniform crossflows has been carried out.Â TheÂ free-end conditionÂ cantilever hasÂ aÂ 34.4Â aspect ratioÂ andÂ aÂ lowÂ mass ratioÂ ofÂ aboutÂ 1.24. TheÂ cylinderÂ freelyÂ oscillates in both inlineÂ andÂ transverseÂ toÂ theÂ flow.Â ReynoldsÂ numberÂ variedÂ fromÂ 10,800Â to 37,800.Â The âjumpÂ phenomenonâÂ was found in the inline motionÂ of the cylinder that agrees well with an existingÂ comparable work.Â At high flow velocities, the 3rdÂ higherÂ harmonicÂ frequenciesÂ ofÂ theÂ cylinderÂ transverseÂ responseÂ became predominant that produce quite different motionÂ characteristicsÂ compared to the otherÂ existingÂ comparableÂ worksÂ withÂ 2-dimensionalÂ bottom-endÂ condition. Generally, the results suggested that the flexible free-hanging cantilever generate differentÂ vortexÂ wakeÂ modeÂ thanÂ either,Â aÂ uniformÂ (aÂ short-rigidÂ flexiblymounted cylinder) or a linear amplitude variation along the spanÂ case (aÂ pivoted cylinder)